Seroprevalence of antibodies against the Infectious Bovine Rinotracheitis virus in extensive cattle herds in three districts of Ayacucho, Peru - Vilchez-Tineo, Caroline (2022)
The aim of this study was to determine the seroprevalence of antibodies against infectious bovine rhinotracheitis virus (IBR) in the districts of Coracora, Chumpi and Pullo of the province of Parinacochas, Ayacucho, during 2018. In total, 460 blood samples were obtained from bovines, male and female, older than 4 months raised under an extensive rearing system. The samples were analyzed with a commercial indirect ELISA kit. The results showed that 59.56 + 4.45% (282/460) of the samples presented antibodies against the IBR virus; and Pullo being the district with the highest seroprevalence (71.58 + 4.09%). Likewise, the zootechnical category and the breed showed a significant statistical association (p<0.05) against the IBR virus.